THE INFLUENCE OF INTELLECTUAL CAPITAL AND SHARIA COMPLIANCE ON ISLAMIC BANKS FINANCIAL PERFORMANCE IN SOUTHEAST ASIA - Putri Syifa Amalia; Desy Norma Safira (AKURAT | Jurnal Ilmiah Akuntansi FE UNIBBA, 2021)
This study examines the effects of Intellectual Capital (IC) and its components (capital employee, human capital, and structural capital) and Sharia Compliance on Islamic banks’ financial performance in Southeast Asia. The value-added intellectual coefficient (VAIC) approach developed by Pulic (1998) is used to determine the IC performance of 30 Islamic banks for the years 2018, 2019, and 2020. The study reveals that human capital and structural capital significantly affect Islamic banks' financial performance. However, this study fails to demonstrate that VAIC, capital employed, and sharia compliance affect Islamic banks’ financial performance. This study contributes to enriching the Islamic economy and finance literature because only a few studies test the factors affecting the Islamic banks’ financial performance in Southeast Asia.